Developing a classification model for graphic devices in early printed books - Ruokkeinen Sirkku; Liira Aino; Varila Mari-Liisa; Norblad Otso; Peikola Matti (Taylor & Francis, 2025)
This article examines visual modes of information transmission in early modern English books. Images, tables, diagrams, and other graphic devices may be used to support or illustrate the text and to communicate information difficult or even impossible to convey via words alone. Previously established models of graphic representation generally focus either on individual devices or device types, or aim to construct taxonomies of present-day materials; little has been done to combine these approaches to create historical taxonomies of visual communication. This article presents a model for classifying graphic devices in early English print, 1473-1700, based on a cross-disciplinary review of previous scholarly work on graphic and visual devices, and discusses the methodology of constructing a taxonomy of devices suitable for historical, diachronic research.